Pengaruh Promosi Terhadap Keputusan Jamaah Umrah Perusahaan Elhanief Tour and Traveldi Banda Aceh - Ikhsan; Refi, Teuku Muana (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2022)
This research was conducted to find out whether there is an influence between Promotion on the Umrah Pilgrims' Decision of the Elhanief Tour and Travel Banda Aceh Company. Primary data comes from questionnaires filled out by Umrah pilgrims as a sample of 96 people. Based on the results of simple linear regression analysis, the variable Y = 11.489 + 0.511X indicates that a constant of 11.489 is the value of the Promotion variable when the Decision variable is zero, or it can be interpreted that if the Promotion variable value is increased by 1 then the Decision variable value increases or increases by 0.511, this shows that the value of the Promotion variable has a positive effect on the Decision variable of 0.511. The results of testing the correlation coefficient (relationship between variables) with symbols obtained R of 0.628 indicating a strong relationship between variables (Promotion and Decisions), while the value of the coefficient of determination or R2 is 0.394, indicating that the effect of the Promotion variable on the Decision variable is 0.394 or if it is percentaged 39.4%, and the remaining 60.6% is influenced by other variables not examined in this study, namely product quality, price and service quality. While the results of testing the hypothesis with the t test obtained tcount > ttable or 7.819 > 1.985 and tsig <5% or 0.00 <0.05. Thus the hypothesis is suspected that promotion influences the decisions of Umrah pilgrims at the Elhanief Tour and Travel company in Banda Aceh City is accepted, and it is suggested to the company to increase promotion again and increase its promotional media so that consumers, especially prospective Umrah pilgrims, are more interested in using the company as an organizer of Umrah trips in future.